The Use of Outdoor Study Methods in Physics Kinematics Learning (A Classroom Action Research) - Muhammad Djajadi (Universitas Muhammadiyah Makassar, 2019)
The research aimed at investigating the improvement of students’ interest in studying physics to students of class XI IPA-1 at SMA Negeri 1 Lappariaja of Bone by utilizing outdoor study method in teaching-learning management. This study was a classroom action research consisted of two cycles of teaching-learning management which covered: (1) the planning, (2) the action stage, (3) the observation stage, and (4) the reflection stage. The collected data covered: (1) the data result of studying physics before conducting the treatment, (2) the data of students’ interests in studying physics, (3) the data result of studying physics of cycle I and II, and (4) the data result of observation/teachers’ notes on each of research cycles. Those data were obtained through questionnaire on the students’ interests in studying physics, the test result of physics cycle I and II, and students’ observation sheets. The data then was analyzed by using quantitative and qualitative analysis. The result of the research shows that there is improvement in studying physics both in cycles I and II to students at SMA Negeri 1 Lappariaja of Bone, the average of the mastery level in studying physics is in high category, and the readiness, the willingness and students’ activeness in following the learning process was improved. The analysis indicated that there was improvement of students’ interests in studying physics at SMA Negeri 1 Lappariaja after conducting the teaching-learning management by utilizing Outdoor study method.Keywords: Outdoor Study Method; Kinematics Physics; Interest in Learning Physics; Learning Outcomes Physics.Penelitian ini bertujuan untuk mengetahui peningkatkan minat dan hasil belajar Fisika siswa kelas XI IPA-1 SMA Negeri 1 Lappariaja Kabupaten Bone dengan menggunakan metode Outdoor Study dalam pengelolaan pembelajaran. Penelitian ini termasuk Penelitian Tindakan Kelas (PTK), yang terdiri dari 2 siklus pengelolaan pembelajaran yang mencakup: (1) perencanaan, (2) tahap pelaksanaan tindakan, (3) tahap observasi, dan (4) tahap refleksi. Data yang dikumpulkan meliputi: (1) data tentang hasil belajar Fisika sebelum pelaksanaan tindakan, (2) data tentang minat belajar Fisika siswa, (3) data tentang hasil belajar Fisika siklus I dan siklus II, dan (4) data hasil observasi/catatan-catatan guru pada setiap siklus penelitian. Data tersebut diperoleh melalui angket tentang minat belajar Fisika siswa, tes hasil belajar Fisika sebelum pelaksanaan tindakan, tes hasil belajar Fisika siklus I dan siklus II, serta lembar observasi belajar siswa. Data tersebut selanjutnya dianalisis dengan menggunakan analisis kuantitatif dan kualitatif. Hasil penelitian menunjukkan bahwa terjadi peningkatan hasil belajar Fisika siswa SMA Negeri 1 Lappariaja Kabupaten Bone baik pada siklus I maupun pada siklus II, rata-rata tingkat penguasaan materi belajar Fisika berada pada kategori tinggi, dan kesiapan, kesungguhan dan keaktifan siswa mengikuti proses pembelajaran semakin meningkat. Analisis menunjukkan bahwa terjadi peningkatan minat dan hasil belajar Fisika siswa SMA Negeri 1 Lappariaja setelah dilakukan pengelolaan pembelajaran dengan menggunakan metode Outdoor Study.Kata kunci: Metode Outdoor Study; Fisika Kinematika; Minat Belajar Fisika; Hasil Belajar Fisika.